Religious attitudes and prosocial behavior: a systematic review of published research - Oviedo, Lluis (Religion, brain & behavior, 2016)
One of the most profound questions in the scientific study of religion is whether or not religion evolved because of its ability to stimulate cooperation, in the sense of in-group mutual help. Historical evidence bearing on this fundamental question is scarce and inconclusive. Relevant empirical and experimental studies have often shown an association between religious variables and the promotion of collaborative attitudes, and sometimes a causal link from religion to cooperation. This study evaluates the quality of the evidence gathered to date. After reviewing previously published theoretical, empirical non-experimental, experimental, experimental-priming, meta-analytic, and hybrid studies, I identify difficulties with current research methodologies, including the lack of standard procedures. I conclude by drawing such conclusions as the existing literature permits regarding the link between religion and prosociality, arguing that religion needs to be understood not as needing to produce prosociality to appear, survive, and develop; but as emerging, surviving, and developing in a complex partnership with moral attitudes and behaviors.